A Taiwanese woman with Dowling-Degos disease: An electron microscopic study with pathophysiological significance - Wei-Tai Yu; Yung-Shun Su; Chih-Hung Lee (Dermatologica Sinica, 2014)
Herein we report a rare case of classical Dowling-Degos disease (DDD) in a Taiwanese woman. A 23-year-old Taiwanese woman presented with generalized hyperpigmentation in irregular and reticulated shapes that she had had since junior high school. Her mother and two sisters had also developed similar pigmentations, starting during their teenage years. The patient did not have previous skin lesions or a history of trauma. She did not have any nail or hair abnormalities. Viewed through a microscope, the hyperpigmented area was found to have elongated rete ridges, the tips of which were found to have a concentration of melanin. Based on the disease onset, family history, clinical and histopathological manifestations, the patient was diagnosed as having DDD. We performed an electron microscopic study revealing a greater number of mature melanosomes in the keratinocytes in the pigmented skin than in those in the nonpigmented skin. The numbers of melanosomes in the melanocytes were similar in both types of skin. This is the first direct comparison of ultrastructural features in pigmented and uninvolved skin in Taiwanese with DDD. We follow the discussion of the case with the differential diagnosis and genetic abnormalities of diseases with reticulate pigmentations. This case report reminds us that keratin 5/14 plays a role in both keratinocyte integrity and melanin transfer.